ANALYSIS OF THE METHODS OF CHOOSING NETWORK STRUCTURE OF THE INTERNET OF THINGS (Conferencea, 2021)
The most common are three- and five-level models of architectures. The first of them is basic and includes the perception level, network and application levels. This model defines the basic idea of IoT, but it is not detailed enough, which is necessary for deeper research. Therefore, architectures with a large number of levels are proposed in the literature. For example, a five-level model that additionally includes processing levels and a transport layer